A DESCRIPTIVE STUDY ON TEACHING SPEAKING TO THE FIRST YEAR STUDENTS OF STM MUHAMMADIYAH TIRTOMOYO WONOGIRI IN 2009/2010 ACADEMIC YEAR - Kurniawati , Yuni (2011)
This research paper aims at describing the implementation of teaching speaking at the first year of STM Muhammadiyah Tirtomoyo, the problems faced by the teacher, and the strategies implemented by the teacher to overcome the problems. This research is a descriptive qualitative research. The researcher collects the data by observing the English class and conducting an interview with the teacher and the students. The data include syllabus, speaking material, field notes and interview scripts. The methods of collecting the data are observation, interview and documents. The result of the research shows that: 1) the objective of teaching speaking in STM Muhammadiyah Tirtomoyo is to develop the communicative competence of the students in four language skills to make the students active in using English both orally and in written forms, 2) the methods used by the teacher in teaching speaking are Direct Method (DM) and Communicative Language Teaching (CLT), 3) the problems faced by the teacher in teaching speaking are the time classroom management, 4) the problems faced by the student in learning speaking are low motivation and students different capability, 5) the strategies used by the teacher are the teacher increases the role of the teacher, the teacher gives more motivation to the students, the teacher gives the time for consultation, and the teacher gives the simple material to the student.